IDENTIFICATION OF SUBSURFACE STRUCTURE USING SEISMIC REFRACTION METHOD AT JANTHO ACEH BESAR - Muhammad Zikrilah; Didik Sugiyanto; Ibnu Rusydy (Jurnal Natural, 2016)
An identification of subsurface structure in the surrounding area of Aceh Besar regent’s office was conducted by using seismic refraction method. The aims of this study are to determine the velocity value between layers in order to describe thesubsurface layer model, to identify the types of rocks on each layer, and to analyze the depth of bedrock layer located in the subsurface. There are 4 tracks with spaces in between each geophone, and on each track, with the width of 3 m. The total spread on the track is 72 m and the farthest shoot point is 36 m from the farthest geophone point.